(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
in this article, the concept of linear equations is introduced using the abstract-deductive method, a definition is given for the equation, then the general form of the equation and methods of its solution are studied, mathematical imagination and logical thinking are discussed through solving the equation